Fast enrichment and detection of circulating tumor cells from large volumes of whole blood of breast cancer patients utilizing a functionalized bioaffinity CTC filtration membrane - Ott, Leonie; Keller, Laura; Bentley, Nathan; Husseini-Wüsthoff, Hümeyra; Werner, René; Zinggeler, Marc; Heidler, Jakoba; Mohammadi, Parinaz Mossahebi; Coith, Cornelia; Pradines, Anne; Stoecklein, Nikolas H.; Löptien, Malte; et al. (International journal of cancer, 2025)
Circulating tumor cells (CTCs) are valuable liquid biopsy analytes as they facilitate an in-depth characterization of disseminated tumors by a simple blood draw. Most CTC assays can only process limited blood volumes, potentially hampering the detection of cells of very low frequency, such as CTCs. Here, we introduce a novel, functionalized nickel filtration membrane, facilitating rapid enrichment of CTCs from various volumes of blood up to 40 mL and leukapheresis products. We validated this assay with different cancer cell lines and compared the performance of our new assay with that of the FDA-cleared CellSearch® system. Performing a comparative analysis of 20 blood samples from patients with metastatic breast cancer, CTCs were found in 19/20 patients (95%), combining the results of both CTC enrichment assays. CTC counts/7.5 mL of blood ranged from 0 to 7280 (CTC filtration membrane) and 0 to 17,190 (CellSearch®). Applying the clinically relevant cut-off of ≥5 CTCs/7.5 mL of blood, 19/20 samples processed with our CTC filter were categorized identically to those analyzed with the CellSearch® system. Furthermore, the filtration time of 40 s for 7.5 mL of blood represents an important advantage of our system, compared to other systems. Importantly, we also demonstrated the feasibility of processing blood samples of up to 40 mL or 2 × 108 nucleated blood cells in 2.5 min. Overall, our new system provides the advantage of performing ultra-rapid enrichment of CTCs and upscaling the volume of blood that can be analyzed, which opens a new avenue for studies on CTC biology.
Zuerst veröffentlicht: 27. Oktober 2025
Gesehen am 09.12.2025